O10 Effect of hemodialysis dose (spKt/V) on survival in patients on maintenance hemodialysis since childhood – a retrospective analysis. Issue 6 (17th May 2019) - Gotta, V; Atkinson, A; Marsenic, O; Pfister, M
Abstract : Background: Hemodialysis (HD) prescription significantly differs between pediatric and adult patients on maintenance HD, resulting in greater difference between prescribed and delivered HD dose. 1, 2 HD dose targets have formally not been evaluated for children, hence targets are mainly derived from adults (spKt/V >1.4; sp: single-pool model of urea distribution, K: urea clearance, t: duration of HD session, V: urea distribution volume). This analysis aimed to evaluate the relationship between delivered dialysis dose and survival in a large cohort of patients having started HD therapy in childhood. Methods: This retrospective analysis included a cohort of patients < 30 years (y) on chronic HD treatment since childhood, having received thrice-weekly HD between 2004 and 2016 in outpatient DaVita dialysis centers. Survival while on HD (death from any cause) was investigated using Kaplan-Meier analysis stratified by age at start of HD (0–2, >2–6, >6–12, and >12–18 y), and three mean delivered dialysis dose levels (spKt/V < 1.4, 1.4–1.6, >1.6). Survival curves between subgroups were compared using the Log-rank test. Results: 1773 patients were included in the analysis, among n=34 having started HD at age of 0–2y, n=57 at >2–6y, n=244 at >6–12y, and n=1438 at >12–18y. Median follow-up on HD ranged between 1.5 (>2–6y) to 4.7 years (>6–12y) with maximal follow-up of 23 years. Death while on HD occurred in 1/34, 6/57, 26/244, and 101/1438 patients during recorded follow-up (p=0.075, n.s.). Patients with mean spKt/V < 1.4 had lower survival on HD than those with spKt/V >1.4–1.6 (p=0.019) and those with spKt/V >1.6 (p=0.035), with 10-year survival estimated to 75% (65.2–86.2%) versus 84.5% (78.5–90.9%) and 85.0% (80.8–89.5%), respectively. Conclusions: This is the first study to report long term survival and its relationship with delivered HD dose in patients starting HD in childhood. Our results support targeting spKt/V(urea)>1.4 in children on chronic HD treatment. References: Gotta V, Marsenic O, Pfister M. Age- and weight-based differences in haemodialysis prescription and delivery in children, adolescents and young adults. Nephrol Dial Transplant 2018 Apr 18. Gotta V, Marsenic O, Pfister M. Understanding urea kinetic factors that enhance personalized hemodialysis prescription in children. ASAIO J 2019 Jan 14. Disclosure(s): M Pfister is a consultant at Quantitative Solutions a Certara Company. V Gotta has been supported for this project by the Research Fund for Junior Researchers, University of Basel, Switzerland. O Marsenic and A Atkinson declare no financial conflict of interest.